P2X2 Receptor Deficiency in Mouse Vestibular End Organs Attenuates Vestibular Function. (21st August 2018) - Takimoto, Yasumitsu; Ishida, Yusuke; Kondo, Makoto; Imai, Takao; Hanada, Yukiko; Ozono, Yoshiyuki; Kamakura, Takefumi; Inohara, Hidenori; Shimada, Shoichi
Highlights: P2X2 receptors were mainly localized in the supporting cells of the vestibular inner ear. Vestibulo-ocular reflex in P2X2 -KO mice was reduced for sinusoidal rotations. P2X2 receptor plays a modulatory role in vestibular function. Abstract: P2X2 receptors are ligand-gated cation channels activated by extracellular ATP that modulate neural transmission in various neuronal systems. Although the function and distribution of P2X2 receptors in the cochlea portion of the inner ear are well established, their physiological role in the vestibular portion is still not understood. Therefore, we investigated P2X2 receptor localization in the peripheral vestibular portion, and assessed their physiological function in vivo using P2X2 receptor knock out (P2X2 -KO) mice. Histological analysis revealed that P2X2 receptors were localized on the epithelial surface of supporting and transitional cells of the vestibular end organs. To examine vestibular function in P2X2 -KO mice, we conducted behavioral tests and tested the vestibulo-ocular reflex (VOR) during sinusoidal rotations. P2X2 -KO mice exhibited significant motor balance impairment in the balance beam test. VOR gain in P2X2 -KO mice was significantly reduced, with no decrease in the optokinetic response. In conclusion, we showed that P2X2 receptors are mainly localized in the supporting cells of the vestibular inner ear, and the loss of P2X2 receptors causes mild vestibular dysfunction. Taken together, our findings suggest that the P2X2 receptor plays a modulatory role in vestibular function.